Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Zum Einstieg: Master-Arbeit zu ökologischer und sozial gerechter Stadtplanung. Ein fiktives Beispiel - Freymuth, Nina (Wissenschaftsläden in der Sozialen Arbeit. Partizipative Forschung und soziale Innovationen)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet’: results from a multistakeholder workshop - Vinoy, Sophie; Goletzke, Janina; Rakhshandehroo, Maryam; Schweitzer, Lisa; Flourakis, Matthieu; Körner, Antje; Alexy, Ute; van Schothorst, Evert M.; Ceriello, Antonio; Zakrzewski-Fruer, Julia K.; Buyken, Anette (European Journal of Nutrition)
Abstract To summarize current knowledge and gaps regarding the role of postprandial glycaemic response in the paediatric population, a workshop was organized in June 2021 by the European branch of the International Life Science Institute (ILSI). This virtual event comprised of talks given by experts followed by in-depth discussions in breakout sessions with workshop participants. The main pre-specified topics addressed by the workshop organizing committee to the invited speakers and the workshop participants were: (1) the role of glycaemic responses for paediatric health, based on mechanistic insights from animal and human data, and long-term evidence from observational and intervention studies in paediatric populations, and (2) changes in metabolism and changes in dietary needs from infancy to adolescence. Each talk as well as the discussions were summarised, including the main identified research gaps. The workshop led to the consensus on the crucial role on health of postprandial glycaemic response in paediatric population. However, a lack of scientific data has been identified regarding detailed glucose and insulin profiles in response to foods commonly consumed by paediatric populations, as well as a lack of long-term evidence including the need for suitable predictors during childhood and adolescence to anticipate health effects during adulthood.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The Effect of Regular Consumption of Reformulated Breads on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Schadow, Alena M.; Revheim, Ingrid; Spielau, Ulrike; Dierkes, Jutta; Schwingshackl, Lukas; Frank, Jan; Hodgson, Jonathan M.; Moreira-Rosário, André; Seal, Chris J.; Buyken, Anette; Rosendahl-Riise, Hanne (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

Professionalisierung von Lehramtsstudierenden für sprachbildenden Fachunterricht im Berufsfeld Ernährung und Hauswirtschaft - Dehn, Freya; Meyer, Anja; Niederhaus, Constanze; Schlegel-Matthies, Kirsten (HiBiFo – Haushalt in Bildung & Forschung)
Aufgrund der heterogenen Schülerschaft im Berufsfeld Ernährung und Hauswirtschaft müssen Studierende für sprachbildenden Fachunterricht professionalisiert werden. Aufbauend auf einer theoretischen Fundierung werden konkrete Umsetzungsbeispiele anhand von drei exemplarischen Online-Modulen für den Ausbildungsberuf Hotelfachfrau/-mann vorgestellt.

Dietary Glycaemic Index Labelling: A Global Perspective. - Barclay, AW; LSA, Augustin; Brighenti, F; Delport, E; Henry, CJ; Sievenpiper, JL; Usic, K; Yuexin, Y; Zurbau, A; TMS, Wolever; Astrup, A; Bulló, M; et al. (Nutrients)

Increased Prevalence of Subclinical Hypothyroidism and Thyroid Autoimmunity in Depressed Adolescents - Hirtz, Raphael; Focker, Manuel; Libuda, Lars; Antel, Jochen; Ozturk, Dana; Kiewert, Cordula; Munteanu, Martin; Peters, Triinu; Fuhrer, Dagmar; Zwanziger, Denise; Thamm, Michael; Hebebrand, Johannes; et al. (The Journal of Clinical Psychiatry)

Rapid amelioration of anorexia nervosa in a male adolescent during metreleptin treatment including recovery from hypogonadotropic hypogonadism - Antel, Jochen; Tan, Susanne; Grabler, Marvin; Ludwig, Christine; Lohkemper, Dominik; Brandenburg, Tim; Barth, Nikolaus; Hinney, Anke; Libuda, Lars; Remy, Miriam; Milos, Gabriella; Hebebrand, Johannes (European Child & Adolescent Psychiatry)
Abstract With this case report we support our medical hypothesis that metreleptin treatment ameliorates starvation related emotional, cognitive and behavioral symptomatology of anorexia nervosa (AN) and show for the first time strong effects in a male patient with AN. A 15.9 year old adolescent with severe AN of eight-month duration was treated off-label with metreleptin. Hyperactivity was assessed with accelerometry. Visual analogue scales (VAS), validated self- and clinician rating scales and lab results tracked changes from baseline to end of the 24-day dosing period and a five-month follow-up. Substantial improvements of mood and eating disorder related cognitions and hyperactivity set in after two days of treatment. During dosing, sub-physiological testosterone and TT3 levels normalized; clinically libido reemerged. Weight did not increase substantially during the dosing period. During follow-up target weight was attained; mood did not deteriorate; hyperactivity ceased. The results substantiate the strong effects seen in female cases and underscore the need for a double-blind placebo-controlled trial to confirm the observed strong, multiple and rapid onset beneficial effects of metreleptin in AN.

Befähigung zur Reflexion und zum Umgang mit Ambiguitäten. Zur Wirksamkeit von Unterricht für "Lebensführung" - Schlegel-Matthies, Kirsten; Wespi, Claudia (Wirksamer Fachunterricht. Eine metaanalytische Betrachtung von Expertisen aus 17 Schulfächern)

Wirksamer Unterricht für Lebensführung. (Unterrichtsqualität: Perspektiven von Expertinnen und Experten 12) - Schlegel-Matthies, Kirsten; Wespi, Claudia

Wörterbuch. Soziale Arbeit - Klünder, Nina (Wörterbuch. Soziale Arbeit)

Relevance of fructose intake in adolescence for fatty liver indices in young adulthood - Perrar, Ines; Buyken, Anette; Penczynski, Katharina J.; Remer, Thomas; Kuhnle, Gunter G.; Herder, Christian; Roden, Michael; Della Corte, Karen; Nöthlings, Ute; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose To examine the association between fructose intake in adolescence and fatty liver indices (hepatic steatosis index (HSI), fatty liver index (FLI)) in young adulthood. Methods Overall, 246 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had a fasting blood sample in adulthood (18–36 years), at least two 3-day weighed dietary records for calculating fructose intakes and other fructose-containing sugars (total (TS), free (FS), added sugar (AS)) as well as two complete 24-h urine samples for calculating sugar excretion (fructose excretion (FE), fructose + sucrose excretion (FE + SE)) in adolescence (males: 9.5–16.5 years; females: 8.5–15.5 years) were analysed using multivariable linear regression analyses. Results On the level of dietary intake, no prospective associations were observed between adolescent fructose intake and both adult fatty liver indices, whereas higher FS intakes were associated with lower levels of HSI ( P trend = 0.02) and FLI ( P trend = 0.03). On the urinary excretion level, however, a higher FE (P trend = 0.03) and FE + SE ( P trend = 0.01) in adolescence were prospectively related to higher adult FLI values. No associations were observed between adolescent sugar excretion and adult HSI. Conclusion The present study does not provide unambiguous support for a detrimental impact of adolescent fructose intake on adult liver health. Nonetheless, further examinations estimating exposure by means of urinary excretion as well as dietary intake levels appear warranted.

The Prospective Association of Dietary Sugar Intake in Adolescence With Risk Markers of Type 2 Diabetes in Young Adulthood - Della Corte, Karen A.; Penczynski, Katharina; Kuhnle, Gunter; Perrar, Ines; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Remer, Thomas; Alexy, Ute; Buyken, Anette (Frontiers in Nutrition)
Purpose: To examine the prospective relevance of dietary sugar intake (based on dietary data as well as urinary excretion data) in adolescent years for insulin sensitivity and biomarkers of inflammation in young adulthood. Methods: Overall 254 participants of the DONALD study who had at least two 3-day weighed dietary records for calculating intakes of fructose, glucose, sucrose, total, free, added sugars, total sugars from sugar-sweetened beverages (SSB), juice, and sweets/sugar or at least two complete 24 h urine samples ( n = 221) for calculating sugar excretion (urinary fructose and urinary fructose + sucrose) in adolescence (females: 9–15 years, males: 10–16 years) and a fasting blood sample in adulthood (18–36 years), were included in multivariable linear regression analyses assessing their prospective associations with adult homeostasis model assessment insulin sensitivity (HOMA2-%S) and a pro-inflammatory score (based on CRP, IL-6, IL-18, leptin, chemerin, adiponectin). Results: On the dietary intake level, no prospective associations were observed between adolescent fructose, sucrose, glucose, added, free, total sugar, or total sugar from SSB, juice or sweets/sugar intake and adult HOMA2-%S ( p > 0.01). On the urinary level, however, higher excreted fructose levels were associated with improved adult HOMA2-%S ( p = 0.008) among females only. No associations were observed between dietary or urinary sugars and the adult pro-inflammatory score ( p > 0.01). Conclusion: The present study did not provide support that dietary sugar consumed in adolescence is associated with adult insulin sensitivity. The one potential exception was the moderate dietary consumption of fructose, which showed a beneficial association with adult fasting insulin and insulin sensitivity.

Changes in chronotype and social jetlag during adolescence and their association with concurrent changes in BMI-SDS and body composition, in the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Krüger, Bettina; Nöthlings, Ute; Buyken, Anette E.; Alexy, Ute (European Journal of Clinical Nutrition)
Abstract Background/objectives Adolescence is a critical period for both the development of overweight and the transition toward a later chronotype, often accompanied by an increase in social jetlag. This study assessed whether changes in chronotype and social jetlag, are linked to changes in body composition during adolescence. Subjects/methods We used data from the DONALD open cohort study, collected between 2014 and 2019, from 213 adolescents (9–17 years at baseline, 45% females) having at least two measures of chronotype and anthropometry ( N = 572). Chronotype was assessed with the Munich Chronotype Questionnaire and defined as: midpoint of sleep corrected for sleep-debt (MSFsc) accumulated over the week (later MSFsc represents later chronotype). Social jetlag (SJL) defines the difference between midpoint of sleep during week and weekend. Calculations for Fat Free Mass Index (FFMI [kg/m 2 )]) and Fat Mass Index (FMI) [kg/m 2 )]) were based on body fat percentage, weight, and height. To analyze the associations, we used linear mixed-effect regression models. Finally, the total cohort was split into three biologically relevant age groups (cut-off set at <12 years, ≥12 to ≤15 years and >15 years). Results Median follow-up was 2.1 years. Overall, change toward a later chronotype was significantly related with an increase in FMI (ß: 0.05, 95% CI: 0.01–0.08). A 1 h increase in social jetlag predicted an increase in BMI-SDS of 0.08 SDS units (95% CI: 0.01–0.14) and in FMI of 0.04 kg/m2 (95% CI: 0.003–0.08). Associations were stronger for the age group ≥12 to ≤15 years ( p for interaction: <0.001). No relationship was found with FFMI. Conclusions Changes in MSFsc and SJL during adolescence were associated with concurrent changes in BMI-SDS and FMI. The age ≥12 to ≤15 years appears to be a sensitive period in which chronobiological changes were clearly associated with increasing body fatness.